Analysis of the interaction between THz waves and low cost plasma detectors for the development of stand-off imaging systems - Pavia, J. P. (2021)
Over the past few years, the Terahertz (THz) band has been seen as quite promising in fields of spectroscopy and imaging. Most of the current manufacturing methods for THz emission and detection devices are limited due to the associated cost and complexity, therefore alternative ways have been sought driven by the availability of new technologies. From recent research in the field of imaging, commercially available Glow Discharge Detectors (GDDs) have been found to be an interesting solution because of their low cost and efficiency in detecting electromagnetic (EM) radiation from microwave to higher frequencies of the electromagnetic spectrum. Several studies have been carried out in the scope of millimeter/sub-millimeter waves to understand how its detection mechanism changes for higher frequencies and how the mechanisms of plasma generation influence the device's performance. In this paper, we aim to study the interaction between THz waves and the structure of a GDD, namely, its reflection, transmission and losses. Numerical modelling of electromagnetics, by solving the Maxwell's equations, has been undertaken for this type of device using different gas pressures of the lamp. Our results show that these devices are not optimized for the THz domain.